Gymnastics festivals around the world and in Brazil: general reflections - PATRÍCIO, Tamiris Lima; BORTOLETO, Marco Antonio Coelho; CARBINATTO, Michele Viviene (Brazilian journal of physical education and sport, 2016)
Abstract The gymnastic festivals are consisted of predominantly non-competitive events, on which several gymnastics possibilities are displayed aiming at fellowship and exchanges between practitioners. The objective of this study is to present some of the top national and international festivals, highlighting relevant aspects of their organizations, frequency and contribution to the maintenance of gymnastic tradition. Finally, we try to sketch some points to consolidate a national festival that would be supported by the different federations, consolidating national identity and promoting the effective gymnastics practice.